THE EFFECT OF COMMITMENT, TRANSFORMATIONAL LEADERSHIP STYLE, AND ORGANIZATIONAL CITIZENSHIP BEHAVIOR ON EMPLOYEE PERFORMANCE - Lia Willyana; Astri Ayu Purwati; Amiruddin M Amin; Muhammad Luthfi Hamzah (Institut Bisnis dan Teknologi Pelita Indonesia, 2024)
The purpose of this research is to analyze commitment, transformational leadership style, and Organizational Citizenship Behavior (OCB) on employee performance. This research was conducted at the company CV. Sersa Jaya Teknologi in Pekanbaru, Riau. The population in this study were all employees, totaling 40 people. Because the population size was relatively small, the entire population was sampled in this study using the census method. The data analysis used is Structural Equation Model (SEM) analysis with PLS. The results of the study explain that transformational leadership style has no positive and insignificant effect on commitment, Organizational Citizenship Behavior has a positive and significant influence on commitment, transformational leadership style has no positive and insignificant effect on employee performance. Organizational Citizenship Behavior has a positive and significant effect on employee performance, commitment does not have a positive and insignificant effect on employee performance at CV. Sersa Jaya Teknologi. Tujuan dari penelitian ini adalah untuk menganalisis komitmen, gaya kepemimpinan transformasional, dan Organizational Citizenship Behavior (OCB) terhadap kinerja karyawan. Penelitian ini dilakukan di perusahaan CV. Sersa Jaya Technology di Pekanbaru, Riau. Populasi dalam penelitian ini adalah seluruh karyawan yang berjumlah 40 orang, karena populasi relatif kecil, maka seluruh populasi dijadikan sampel dalam penelitian ini menggunakan metode sensus. Analisis data yang digunakan adalah analisis Model Persamaan Struktural (SEM) dengan PLS. Hasil penelitian menjelaskan bahwa gaya kepemimpinan transformasional tidak memiliki pengaruh positif dan tidak signifikan terhadap komitmen, Organizational Citizenship Behavior memiliki pengaruh positif dan signifikan terhadap komitmen, gaya kepemimpinan transformasional tidak memiliki pengaruh positif dan tidak signifikan terhadap kinerja karyawan. Organizational Citizenship Behavior memiliki pengaruh positif dan signifikan terhadap kinerja karyawan, komitmen tidak memiliki pengaruh positif dan tidak signifikan terhadap kinerja karyawan di CV. Sersa Jaya Technology.